The RAS and YAP1 dance, who is leading? - Corbo, Vincenzo (EMBO J, 2014)
The Hippo-signaling effector YAP1 was recently found to compensate for oncogenic RAS in certain neoplasms, suggesting so far unanticipated molecular interplays between these major signaling routes. A new study in this issue of The EMBO Journal details KRAS-dependent control of YAP1 stability as well as positive feedback regulation via the RAS/YAP1/EGFR-ligand axis as novel molecular mechanisms that could become exploitable for therapeutic strategies.